Computational cardiology and risk stratification for sudden cardiac death: one of the grand challenges for cardiology in the 21st century. (9th June 2016) - Hill, Adam P.; Perry, Matthew D.; Abi‐Gerges, Najah; Couderc, Jean‐Philippe; Fermini, Bernard; Hancox, Jules C.; Knollmann, Bjorn C.; Mirams, Gary R.; Skinner, Jon; Zareba, Wojciech; Vandenberg, Jamie I.
Abstract : Proposed roadmap for computational cardiology. A, general approach for clinical application of computational cardiology outlining three stages of development: (i) development of baseline models; (ii) disease specific simulations; and (iii) translation. At each state black arrows represents the iterative process of in silico simulation and in vitro/in vivo validation that is critical for successful implementation. The human ventricular mesh was provided by Dr Mikael Wallman and Professor Blanca Rodriguez, and developed as described in Wallman et al . 2014. B, specific priority goals for convergence of computational and clinical cardiology. Expanded discussion of specific goals is presented in the section headed The future: moving computational cardiology into the clinic. Abstract: Risk stratification in the context of sudden cardiac death has been acknowledged as one of the major challenges facing cardiology for the past four decades. In recent years, the advent of high performance computing has facilitated organ‐level simulation of the heart, meaning we can now examine the causes, mechanisms and impact of cardiac dysfunction in silico . As a result, computational cardiology, largely driven by the Physiome project, now stands at the threshold of clinical utility in regards to risk stratification and treatment of patients at risk of sudden cardiac death. In this white paper, we outline a roadmap of what needs to be done to make this translational step, using the relatively well‐developed case of acquired or drug‐induced long QT syndrome as an exemplar case.